REACTUALIZING THE VALUE OF SOCIAL JUSTICE AS AN ETHICAL GUIDELINE FOR POLITICAL CONDUCT IN INDONESIA - Eva Elista; Sunarso (SOSIOEDUKASI, 2026)
This study examines the importance of reactualizing the value of social justice as an ethical guideline in political behavior in Indonesia. Social justice, as contained in the fifth principle of Pancasila, should serve as a fundamental principle that guides every policy and political action in order to create an equal, prosperous, and civilized society. However, in reality, political practices in Indonesia are still largely characterized by corruption, nepotism, and weak leadership ethics, which hinder the achievement of these goals. This study employs a qualitative approach using a literature review method to analyze the concepts of social justice and political ethics, as well as the relationship between the two in strengthening substantive democracy. The discussion focuses on the challenges faced in implementing the value of social justice, as well as strategies for its reactualization through political education, law enforcement, and the strengthening of public participation. The results of the analysis show that the reactualization of the value of social justice is essential to improving deviant political behavior and realizing a system of governance that is more just, transparent, and civilized.